Arrhythmia Mechanism and Dynamics in a Humanized Mouse Model of Inherited Cardiomyopathy Caused by Phospholamban R14del Mutation. Issue 6 (10th August 2021) - Raad, Nour; Bittihn, Philip; Cacheux, Marine; Jeong, Dongtak; Ilkan, Zeki; Ceholski, Delaine; Kohlbrenner, Erik; Zhang, Lu; Cai, Chen-Leng; Kranias, Evangelia G.; Hajjar, Roger J.; Stillitano, Francesca; et al.
Abstract : Background: Arginine (Arg) 14 deletion (R14del) in the calcium regulatory protein phospholamban (hPLN R14del ) has been identified as a disease-causing mutation in patients with an inherited cardiomyopathy. Mechanisms underlying the early arrhythmogenic phenotype that predisposes carriers of this mutation to sudden death with no apparent structural remodeling remain unclear. Methods: To address this, we performed high spatiotemporal resolution optical mapping of intact hearts from adult knock-in mice harboring the human PLN WT (wildtype [WT], n=12) or the heterozygous human PLN R14del mutation (R14del, n=12) before and after ex vivo challenge with isoproterenol and rapid pacing. Results: Adverse electrophysiological remodeling was evident in the absence of significant structural or hemodynamic changes. R14del hearts exhibited increased arrhythmia susceptibility compared with wildtype. Underlying this susceptibility was preferential right ventricular action potential prolongation that was unresponsive to β-adrenergic stimulation. A steep repolarization gradient at the left ventricular/right ventricular interface provided the substrate for interventricular activation delays and ultimately local conduction block during rapid pacing. This was followed by the initiation of macroreentrant circuits supporting the onset of ventricular tachycardia. Once sustained, these circuits evolved into high-frequency rotors, which in their majority were pinned to the right ventricle. These rotors exhibited unique spatiotemporal dynamics that promoted their increased stability in R14del compared with wildtype hearts. Conclusions: Our findings highlight the crucial role of primary electric remodeling caused by the hPLN R14del mutation. These inherently arrhythmogenic features form the substrate for adrenergic-mediated VT at early stages of PLN R14del induced cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.